ANALISIS PENGETAHUAN REMAJA TENTANG KEPENDUDUKAN DAN KELUARGA BERENCANA DI KELURAHAN TEGAL REJO KECAMATAN MEDAN PERJUANGAN - Yuspah Hanum, dkk (JURNAL KELUARGA SEHAT SEJAHTERA, 2015)
ABSTRACT In adolescence curiosity about sexual problems is very important in the formation of a new, more mature relationship with the opposite sex. Information about sexual problems should be started, so that teens do not seek information from another person or from sources that are not clear or even wrong at all. Giving information about sexual problems becomes even more important in view of teenagers who are sexually active in potency, because it is associated with hormone-influenced sexual drive and often do not have enough information about their own sexual activity. Of course it will be very harmful to the mental development of a teenager when he does not have the right knowledge and information. Facts show that the majority of our youth do not know the impact of sexual behavior that they do, often adolescents are not mature to have sexual intercourse especially if you have to bear the risk of the sexual relationship. Kata Kunci : Pengetahuan, Remaja, Kependudukan, Keluarga Berencana.